Max Plus Algebra and It’s Aplication: Model of Simple Production System - Nasrulyati, Tri Siwi (Jurusan Matematika FMIPA Universitas Jember, 2017)
This paper discusses the basic understanding of max plus algebra and an example of its application will be given. Next will be discussed a simple production system model with three machines.